1992
DOI: 10.1159/000111658
|View full text |Cite
|
Sign up to set email alerts
|

Xenogenic Transplantation into Newborn Rodent Brain: Neovascularization of the Graft by the Host

Abstract: Neoangiogenesis of transplants implanted into the brains of newborn rodent hosts was evaluated by immunohistochemistry for 2 weeks after the operation. The use of species-specific antibodies directed against mouse endothelial cells demonstrated the respective participation of the host and the donor in the formation of new vessels in the graft after crossed rabbit into mouse and mouse into rat transplantation experiments. We show that blood vessels made by host endothelial cells begin to penetrate the transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Reappearance of human endothelial cells in the 2-and 3-month-old grafts strongly suggests that they were substained at an immature stage rather than eliminated. In that sense, our results compare with those obtained by Broadwell et al (1987, 199 1) and Dusart et al (1989), who demonstrated that blood circulation occurs after a delay of more than a week in allo-and xenografts in rodents, even though endothelial cells are present at earlier stages (Lawrence et al, 1984;Krum and Rosenstein, 1988;Krum et al, 199 1;Mrejen et al, 1992). The main difference between the present results and those quoted above is the length of the delay before vascularization, which in the humanto-rat xenografts of this study amounted to more than a month.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Reappearance of human endothelial cells in the 2-and 3-month-old grafts strongly suggests that they were substained at an immature stage rather than eliminated. In that sense, our results compare with those obtained by Broadwell et al (1987, 199 1) and Dusart et al (1989), who demonstrated that blood circulation occurs after a delay of more than a week in allo-and xenografts in rodents, even though endothelial cells are present at earlier stages (Lawrence et al, 1984;Krum and Rosenstein, 1988;Krum et al, 199 1;Mrejen et al, 1992). The main difference between the present results and those quoted above is the length of the delay before vascularization, which in the humanto-rat xenografts of this study amounted to more than a month.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, acidic FGF, which is the principal angiogenic factor in the brain, is highly conserved among vertebrates (Risau et a1.,1988). Otherwise, in other models of xenografts, angiogenesis occurs clearly within 10 d (mouse to rat, Nakano et al, 1989;Mrejen et al, 1992;rabbit to mouse, Mrejen et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation